HYPNODIALYSIS FOR ANXIETY RELIEF AND ADHERENCE TO MEDICATION, KIDNEY DIET AND FLUID INTAKE IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Siti Hajar Wati; Mardiyono Mardiyono; Warijan Warijan (Belitung Nursing Journal, 2017)
Objective: To examine the effectiveness of hypnodialysis on anxiety levels and adherence to medication, kidney diet and fluid intake in patients with chronic kidney disease. Methods: This was a randomized controlled trial study conducted from November to December 2016. Thirty respondents recruited using simple random sampling, which 17 respondents assigned randomly in the experiment and control group. The Hamilton Anxiety Rating Scale (HARS), Morisky scale, adherence to kidney diet questionnaire, adherence to fluid intake questionnaire were used as instruments for this study. Paired t-test and repeated ANOVA were used for data analysis. Results: Findings showed that there was a statistically significant effect of hypnodialysis in reducing anxiety levels and improving adherence to medication, kidney diet, and fluid intake in patients with chronic kidney disease with p-value 0.000 (<0.05), which its effect started from day 7 (posttest 1). Conclusion: Hypnodialysis may decrease anxiety levels and improve medication adherence, kidney diet and fluid intake. Therefore, hypnodialyis can be alternative treatment for patients with chronic kidney disease.